Inoculum monitoring, fruit susceptibility to infection and fungicide efficacy for citrus black spot control during fruit development in sweet orange orchards - Fialho, Régis de Oliveira (2021)
The pathogen Phyllosticta citricarpa produces ascospore and pycnidiospore, which play an important role in the epidemiology of citrus black spot (CBS) in Brazilian conditions. However, the detection and quantification of the two types of P. citricarpa inoculum during the season are poorly studied. Moreover, the citrus fruit susceptibility to P. citricarpa infections as well as the critical period to CBS control have been reported as variable in different CBS-affected areas worldwide. Therefore, this study aimed to: (i) monitor and quantify both ascospores and pycnidiospores in commercial orchards; (ii) determine the susceptibility of sweet orange fruit by artificial inoculation of P. citricarpa at different developmental stages in commercial orchards, and (iii) identify the efficacy of copper oxychloride and pyraclostrobin fungicides sprayed at different fruit developmental stages for CBS control in commercial orchard. Monitoring of P. citricarpa inoculum was performed in two ‘Valencia’ sweet orange orchards during two seasons in São Paulo (SP) state, Brazil, by using young citrus trees as spore trap combined with quantitative polymerase chain reaction (qPCR) analyses. Traps kept under the canopy of trees had up to 407 ITS copies/cm2, while the peak for traps kept outside the canopy was about 60 ITS copies/cm2. P. citricarpa ITS copies were mainly detected between October to March, and the peaks were usually found from November to February. Fewer than 20 ITS copies/cm2 were detected from March to July. The amount of ITS was related to rainy days (≥ 5mm) and leaf wetness duration. The susceptibility of fruit to P. citricarpa infections by artificial inoculation from October to July was assessed in two ‘Valencia’ orchards in SP. CBS symptoms and fruit drop were observed in high levels when fruit were inoculated from October to February, while from March to July the symptoms were expressed in low intensities. The highest CBS severities were 20, 15 and 10% reached on fruit inoculated with 105 pycnidiospore/mL 10 times from October to July, only in November or only in December, respectively. The efficacy of copper or pyraclostrobin spray at different times after petal fall was assessed in Natal sweet orange in SP. Both fungicides applied only once consistently reduced CBS symptoms from December to March. CBS incidences were reduced ~50% with copper fungicide from petal fall through June/August, while reductions for QoI fungicide were 80 to 90%. The absence of a single QoI application for 38-to-42 days did not result in CBS increase, whereas trees without copper for a period of 26-to-30 days from December to March had greater CBS intensity on fruit. Taking into account the consistence of the results obtained in different trials that assessed not only the inoculum but also the susceptibility of fruit and efficacy of fungicides, CBS control failures may not occur mainly from November to February due to the presence of conditions highly favorable for fruit infections and CBS occurrence in SP sweet orange orchards.